Planning and managing ATM networks - Minoli, Daniel 1952- (MANNING, 1997)
Planning and Managing ATM Networks covers strategic planning, initial deployment, overall management, and the day-to-day operation of ATM networks. It defines steps to determine requirements for ATM networks, as ATM implementation becomes widespread in the corporate enterprise network. It describes fundamental management concepts and procedures, including fault and configuration management, performance management, accounting, and security. This book is an indispensable reference for the networking engineer, designer, planner, and manager, as well as a working framework for anyone who plans, oversees, and implements networks. It is also a unique, clearly written guide for corporate staff.